Analysis of the Experimental Data for Pure and Diluted [FexZn1–x(bbtr)3](ClO4)2 Spin‐Crossover Solids in the Framework of a Mechanoelastic Model. Issue 5 (3rd January 2013) - Chakraborty, Pradip; Enachescu, Cristian; Hauser, Andreas
Abstract: The mechanoelastic model is applied to reproduce the experimental relaxation and thermal transition curves as determined for crystals of pure and diluted [Fe x Zn1– x (bbtr)3 ](ClO4 )2 ∞ [bbtr = 1, 4‐di(1, 2, 3‐triazol‐1‐yl)butane] spin‐crossover systems. In the mechanoelastic model, the spin‐crossover complexes are situated in a hexagonal planar lattice, which is similar to the 2D coordination polymer with (3, 6) network topology of [Fe(bbtr)3 ](ClO4 )2 . These complexes are linked by springs, which simulate the elastic interactions between them. Owing to the change in volume of the complexes during the spin transition, an elastic force accompanies the switch of every complex. This force propagates through the entire lattice and causes a shift of all molecules in the system and thus results in a new nuclear configuration. First, the ability of the model to reproduce various shapes of thermal transition and relaxation curves in pure compounds is analyzed; these range from gradual to very steep and include hysteresis behavior for the former and from single exponential to sigmoidal or with several steps for the latter. A structural phase transition can also be accounted for by changing the shape of the sample at a fixed temperature from a regular to an elongated hexagon. Furthermore, the effect of adding Zn as a dopant in a mixed crystal series is discussed. The role of dopants on the cluster evolution is also analyzed directly and by using the correlation factor. Abstract : The mechanoelastic model is applied to reproduce various shapes of thermal transition and relaxation curves obtained for crystals of pure and diluted [Fe x Zn1– x (bbtr)3 ](ClO4 )2 ∞ spin‐crossover systems. The effect of adding Zn as dopant in a mixed crystal series is discussed. The role of dopants on the cluster evolution is analyzed directly and using the correlation factor.